2008
DOI: 10.1038/modpathol.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological features and prognostic significance of the micropapillary pattern in lung adenocarcinoma

Abstract: The micropapillary pattern is characterized by small papillary tufts with no fibrovascular core lying in spaces and has been reported as an aggressive variant of carcinoma in several organs. We investigated the histopathobiological properties of the micropapillary pattern with immunohistochemistry, serial sections, and electron microscopy in lung adenocarcinoma. We further analyzed its clinicopathological character and prognosis. The subjects included 383 adenocarcinoma cases, of which 184 (48%) were micropapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
116
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 24 publications
(21 reference statements)
14
116
1
Order By: Relevance
“…The presence of a micropapillary pattern in lung adenocarcinomas reportedly correlates with increased propensity for metastasis, pleural invasion, and decreased survival among stage I patients. [22][23][24] Molecular analysis of the 41 lung adenocarcinomas with a micropapillary-predominant pattern in our study cohort revealed ALK rearrangements in 19 (46%) followed by KRAS mutations in 6 (15%) (data not shown), whereas others have demonstrated a strong association between EGFR mutations and the micropapillary pattern in previous studies with resection specimens. 25,26 These findings complement the evolving molecular characterization of micropapillary lung adenocarcinomas and support the recent recommendations by the IASLC/ATS/ERS to consider micropapillary architecture to be a distinct and potentially biologically significant histologic subtype.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The presence of a micropapillary pattern in lung adenocarcinomas reportedly correlates with increased propensity for metastasis, pleural invasion, and decreased survival among stage I patients. [22][23][24] Molecular analysis of the 41 lung adenocarcinomas with a micropapillary-predominant pattern in our study cohort revealed ALK rearrangements in 19 (46%) followed by KRAS mutations in 6 (15%) (data not shown), whereas others have demonstrated a strong association between EGFR mutations and the micropapillary pattern in previous studies with resection specimens. 25,26 These findings complement the evolving molecular characterization of micropapillary lung adenocarcinomas and support the recent recommendations by the IASLC/ATS/ERS to consider micropapillary architecture to be a distinct and potentially biologically significant histologic subtype.…”
Section: Discussionmentioning
confidence: 52%
“…As solid and micropapillary patterns of lung adenocarcinoma have been reported to have an increased propensity for metastasis, it is possible that any statistical predilection that ALK þ tumors show for a solid or micropapillary pattern is diminished by the overall higher prevalence of solid and micropapillary patterns at metastatic sites. 22,23,27 Although ALK þ primary lung adenocarcinomas were associated with the presence of hepatoid tumor cells and psammoma bodies, these associations also failed to be preserved in metastatic tumors. It is currently unclear why these morphologic features help distinguish ALK rearrangements in primary lung tumors but not in metastatic tumors.…”
Section: Nishino Et Almentioning
confidence: 99%
“…28,29 The adverse prognosis associated with the micropapillary pattern, confirms observations in multiple previous studies and supports the addition of this new subtype to the classification. 10,11,[30][31][32][33] However, varied criteria for the diagnosis have been used with percentage of the micropapillary component including as little as 6% of the total tumor and none of these studies have utilized comprehensive histological subtyping to define this subgroup according to the predominant subtype showing comparison with survival of the other histological subtypes as we have done. 10,11,[30][31][32][33] Our finding that colloid adenocarcinomas also fit into this poor prognostic group was somewhat surprising as these tumors are often regarded as well-differentiated tumors, but this is the largest series of these tumors reported where survival analysis compared outcome with other adenocarcinoma histological types.…”
Section: Discussionmentioning
confidence: 99%
“…18,23,40,45 The aggressive behavior of the cells that produce micropapillae was attributed to their high proliferative activity, stimulation of angiogenesis, and anchorageindependent growth. 14,20 Vasculogenic mimicry was recently described in canine inflammatory mammary cancers and previously in several human malignant tumors, such as breast carcinomas, gliomas, melanomas, and hepatocellular carcinomas. 6,46 Human studies suggested that it furnishes an additional blood supply to the tumor and facilitates hematogenous dissemination.…”
Section: Discussionmentioning
confidence: 99%